Outcomes of Older Hospitalized Patients Requiring Rapid Response Team Activation for Acute Deterioration. Issue 12 (December 2018) - Fernando, Shannon M.; Reardon, Peter M.; McIsaac, Daniel I.; Eagles, Debra; Murphy, Kyle; Tanuseputro, Peter; Heyland, Daren K.; Kyeremanteng, Kwadwo
Abstract : Objectives: Rapid response teams are groups of healthcare providers that have been implemented by many hospitals to respond to acutely deteriorating patients admitted to the hospital wards. Hospitalized older patients are at particular risk of deterioration. We sought to examine outcomes of older patients requiring rapid response team activation. Design: Analysis of a prospectively collected registry. Setting: Two hospitals within a single tertiary care level hospital system between 2012 and 2016. Patients: Five-thousand nine-hundred ninety-five patients were analyzed. Comparisons were made between older patients (defined as ≥ 75 yr old) and younger patients. Interventions: None. Measurements and Main Results: All patient information, outcomes, and rapid response team activation information were gathered at the time of rapid response team activation and assessment. The primary outcome was in-hospital mortality, analyzed using multivariate logistic regression. Two-thousand three-hundred nine were older patients (38.5%). Of these, 835 (36.2%) died in-hospital, compared with 998 younger patients (27.1%) (adjusted odds ratio, 1.83 [1.54–2.18]; p < 0.001). Among patients admitted from home, surviving older patients were more likely to be discharged to a long-term care facility (adjusted odds ratio, 2.38 [95% CI, 1.89–3.33]; p < 0.001). Older patients were more likely to have prolonged delay to rapid response team activation (adjusted odds ratio, 1.79 [1.59–2.94]; p < 0.001). Among patients with goals of care allowing for ICU admission, older patients were less likely to be admitted to the ICU (adjusted odds ratio, 0.66 [0.36–0.79]), and less likely to have rapid response team activation during daytime hours (adjusted odds ratio, 0.73 [0.62–0.98]; p < 0.001). Conclusions: Older patients with in-hospital deterioration requiring rapid response team activation had increased odds of death and long-term care disposition. Rapid response team activation for older patients was more likely to be delayed, and occur during nighttime hours. These findings highlight the worse outcomes seen among older patients with in-hospital deterioration, identifying areas for future quality improvement. Abstract : Supplemental Digital Content is available in the text.